Prevalence, Antibiotic Susceptibility Pattern and Associated Factors of Streptococcus pyogenes among Pediatric Patients with Acute Pharyngitis in Sidama, Southern Ethiopia - Alemitu Beyene Gebre; Demissie Assegu Fenta; Abel Abera Negash; Betelihem Jima Hayile (International Journal of Microbiology)
Background. Streptococcus pyogenes is the most frequent cause of pharyngitis and skin infections in children and causes immune complications like rheumatic fever and rheumatoid heart disease (RHD), particularly in developing countries like Ethiopia. The aim of this study was to determine the prevalence, antibiotic resistance pattern, and associated factors of Streptococcus pyogenes among pediatric patients suspected of acute pharyngitis in Sidama Region, Southern Ethiopia. Methods. A cross-sectional study was conducted on 213 acute pharyngitis suspected pediatric patients from April to September 2022 at Hawassa University Compressive Specialized Hospital and Yirgalem Hospital. Sociodemographic and clinical data were collected using a structured questionnaire. A throat swab was cultured to isolate S. pyogenes, and antimicrobial susceptibility testing was done using standard bacteriological techniques. Data were analyzed using SPSS version 25, and P value of <0.05 was considered as statistically significant. Result. Out of 213 throat swabs cultured, 22 (10.3%) with 95% CI (6.6–14.6%) were S. pyogenes positive. All isolates of S. pyogenes were sensitive to penicillin and amoxicillin. In contrast, 8 (36.4%) isolates exhibited resistance to tetracycline, 7 (31.8%) to ceftriaxone, 6 (27.3%) to erythromycin, and 5 (22.7%) isolates showed multidrug resistance. The presence of palatal petechiae (P=0.037) and tonsillar swelling or exudate (P=0.007) were significantly associated with S. pyogenes carriage in children suspected of having acute pharyngitis. Conclusion. In this study, the prevalence of S. pyogenes among children suspected with acute pharyngitis was low compared to other studies. The isolates showed a high level of resistance to commonly used antibiotics. Therefore, the treatment of pediatric acute S. pyogenes pharyngitis should depend on an antimicrobial susceptibility test. Furthermore, evaluation of S. pyogenes pediatric acute pharyngitis risk factors and tracking of antibiotic resistance are crucial in the controlling of pediatric acute S. pyogenes pharyngitis.